Current concepts of elbow-joint disorders and their treatment - Inagaki, Katsunori (Springer Japan, 2013)
BACKGROUND: Recently, many studies have emphasized the importance of the comprehension of detailed functional anatomy and biomechanics of the elbow and its significant contribution in facilitating good functional outcomes of conservative and surgical treatment in the field of elbow disorders. METHODS: The most common disease of elbow disorders and their treatment was reviewed. RESULTS: Lateral epicondylitis of the elbow, is defined as a microscopic tear of extensor carpi radialis brevis tendon, and microscopic findings show immature reparative tissue (angiofibroblastic hyperplasia). The patient needs coordinated rehabilitation, range-of motion-exercise, stretching, and bracing in the second phase. Ninety-five percent of patients with lateral epicondylitis heal spontaneously or conservatively. The medial collateral ligament injury of the elbow is most common in the overhead-throwing athlete. Jobe’s procedure, the original reconstruction technique, and its modifications in bone-tunnel creation, allow a tendon graft to be wound in a figure-eight configuration through the tunnels. Further modification of Jobe’s procedure in bone-tunnel configuration reduced the total number of tunnels and facilitates easier graft tensioning. Outcomes with these reconstruction techniques have proven effective in returning high-level throwing athletes back to their sport. Arthroscopic surgery for the elbow in the throwing athlete has evolved and has proven successful results. Arthroscopic treatment includes debridement of posteromedial synovitis, loose-body removal, and excision of the olecranon spur. Posteromedial elbow impingement is also a source of disability in the overhead-throwing athlete. Twenty-five percent of these patients require a medial collateral ligament reconstruction after removal of a posteromedial bony spur. Linked and unlinked total elbow arthroplasty are successful treatment procedures for patients with rheumatoid arthritis, posttraumatic osteoarthritis, and elderly patients with comminuted distal humeral fractures and the salvage of distal humeral nonunion. Proper selection and implantation of prostheses are also important to achieve good functional outcome and longevity. CONCLUSION: The success of treatment of elbow disorders depends greatly on surgical design and technique, both of which require comprehensive knowledge of detailed anatomy and biomechanics of the elbow.